Brexit and UK Energy Security: Perspectives from Unconventional Gas Investment and the Effects of Shale Gas on UK Energy Prices - Elijah Acquah-Andoh; Augustine O. Ifelebuegu; Stephen C. Theophilus (Energies, 2019)
Many aspects of the present and future effects on the UK economy, industry, and households, of Brexit have been researched. One thing which appears certain about Brexit is the shadow of uncertainty it casts on the future of business in the UK and its telling effects on the UK economy. It is believed that Brexit has negatively affected the level of investments in the UK, including investments in energy and crucially the upstream oil and gas, with the UK North Sea being starved of investments since 2014, leading already to increased energy bills. The UK is a net importer of natural gas—a major source of its energy, with some dependence on supplies from interconnectors from Europe. At the same time, UK energy companies participate in the common energy market which enables them to undertake arbitrage trading under the common market rules. However, both of these benefits could be lost under a Brexit scenario where the UK and EU come to a no-deal or hard border arrangement. Meanwhile, domestic production of energy in the UK has declined for nearly two decades now and import bills for natural gas are growing—they were £14.2 billion in 2017; £11.7 billion in 2016 and £13.4 billion in 2015—with Government projections indicating an upward trajectory for natural gas imports. It is however believed that the UK has great potential to exploit shale gas to her advantage in order to reduce her reliance on foreign energy which is: (1) less predictable in terms of supply and price affordability and (2) dependent on exchange rates—a primary means through which energy prices increased in 2016/17 post-Brexit referendum vote. The current study extends discussions on shale gas to cover a review of the potential of natural gas from shale formations to cushion UK households against further erratic gas prices due to Brexit and also assesses the potential effects Brexit may have had on the level of investments in shale gas, in order to suggest policy options for government consideration. Contrary to popular studies, we find evidence to suggest that shale gas has the potential to reduce energy prices for UK businesses and households at commercial extractions, under both hard and soft Brexit scenarios, but with more benefits under hard Brexit. Importantly, we find that from 2008 to 2017, average UK net export of natural gas was 5,191 GWh per year to the EU. We also find and argue that Brexit may have starved the nascent fracking industry of investments in a similar way it did to investments in conventional oil and gas and could have increased investor risk premium for shale gas development, the ultimate effect of which was a categorisation of fracking (company stock) as riskier asset for investors on the London Stock Exchange. We recommend that shale gas development be expedited to maximise its benefits to UK energy consumers post-Brexit or economic benefits from the resource could be diminished by rising operator costs due to delays and effects of the public’s perceived negative opinion of the method of extraction.